Cement Replacement Materials Properties, Durability, Sustainability - Ramezanianpour, Ali Akbar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The aim of this book is to present the latest findings in the properties and application of Supplementary Cementing Materials and blended cements currently used in the world in concrete. Sustainability is an important issue all over the world. Carbon dioxide emission has been a serious problem in the world due to the greenhouse effect. Today many countries agreed to reduce the emission of CO2. Many phases of cement and concrete technology can affect sustainability. Cement and concrete industry is responsible for the production of 7% carbon dioxide of the total world CO2 emission. The use of supplementary cementing materials (SCM), design of concrete mixtures with optimum content of cement and enhancement of concrete durability are the main issues towards sustainability in concrete industry.
Natural Pozzolans -- Fly Ash -- Granulated Blast Furnace Slag -- Silica Fume -- Metakaolin -- Rice Husk Ash -- LimeStone -- The Role of Supplementary Cementing Materials on Sustainable Development.
Keywords: Geography; Mineralogy; Building construction; Earth Sciences; Mineralogy; Building Materials; Ceramics, Glass, Composites, Natural Methods